Strategies to increase response rate and reduce non-response bias in population health research: a series of randomised controlled trials during a large COVID-19 study - Atchison, CJ; Gilby, N; Pantelidou, G; Clemens, S; Pickering, K; Chadeau-Hyam, M; Ashby, D; Barclay, WS; Cooke, G; Darzi, A; Riley, S; Donnelly, C; et al. (JMIR Publications, 2025)
Background: High response rates are needed in population-based studies as non-response reduces effective sample size and bias affects accuracy and decreases generalizability of the study findings. Objectives: We tested different strategies to improve response rate and reduce non-response bias in a national population-based COVID-19 surveillance programme in England, UK. Methods: Over 19 rounds, a random sample of individuals aged 5 years and older from the general population in England were invited by mail to complete an online questionnaire and return a swab for SARS-CoV-2 testing. We carried out several nested randomised controlled experiments to measure the impact on response rates of different interventions, including (1) variations in invitation and reminder letters and text messages, and (2) the offer of a conditional monetary incentive to return a swab, reporting absolute changes in response and relative response rate (RRR with 95% Confidence Intervals). Results: Monetary incentives increased the response rate (completed swabs returned as a proportion of the number of individuals invited) across all age groups, sex at birth and area deprivation with the biggest increase among the lowest responders, namely teenagers and young adults and those living in more deprived areas. With no monetary incentive, the response rate was 3.4% in participants aged 18-22 years, increasing to 8.1% with a £10 incentive, 11.9% with £20, and 18.2% with £30 (RRR 2.4 (95% CI 2.0, 2.9), 3.5 (95% CI 3.0, 4.2) and 5.4 (95% CI 4.4, 6.7) respectively). Non-monetary strategies had a modest, if any, impact on response rate. The largest effect was observed for changing the swab reminder approach. Those receiving an additional text message were more likely to return a completed swab compared to those receiving the standard approach, 73.3% v 70.2%: percentage difference 3.1% (95% CI 2.2%, 4.0%). Conclusions: Conditional monetary incentives improved response rate to an online survey which required the return of a swab test, particularly for younger age groups. Used in a selective way, incentives may be an effective strategy for improving sample response and representativeness in population-based studies.